Glass substrate surface wet chemical metallization method
The preparation of aqueous SAPL dispersion solution by full-wet chemistry solves the problem of insufficient adhesion on the surface of the glass substrate, and achieves uniform coverage and high adhesion on the surface of the glass substrate, which is suitable for the application of multifunctional electronic devices.
Patent Information
- Application Number
- CN202411249635.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-31
AI Technical Summary
Due to its flat and chemical inert surface, it is difficult to roughen sufficiently by existing physical or chemical methods, resulting in insufficient adhesion of metal films, which hinders the application of glass substrates in electronic systems.
The aqueous SAPL molecular dispersion solution is prepared by all-wet chemistry method, which contains adhesion-promoting and autocatalytic active metal oxide nanoparticles. The SAPL film is formed by high-temperature treatment, providing strengthened bonding and catalytic active sites, and improving the adhesion of the metal film. .
The uniform coverage of the glass substrate surface and the adhesion force are improved, and the problems of uniform coverage of the adhesion layer and conductive seed layer of the microstructured glass substrate are solved, which reduces costs and provides a metal layer with high adhesion and purity.
Smart Images

Figure CN119219340A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to a surface modification technology involving glass substrate and glass substrate surface processed with microstructure or microstructure surface for overall or partial "conformal" metallization.
[0002] The present invention can be directly applied to, but not limited to, the fields of glass substrate surface decoration, high thermal conductivity glass, electrically heatable glass, wireless energy supply glass substrate, electromagnetic shielding glass, electronic substrate glass, glass-based biosensor electrodes and signal transmission layers, integrated circuit packaging substrates, etc. Background Art
[0003] With the rapid rise of mobile communications and mobile Internet, Internet of Things (IoT) and artificial intelligence, electronic devices / modules are developing towards multifunctional integration, high performance, lightweight, low energy consumption and low cost. Glass has become an extremely attractive substrate or adapter material in many application fields such as integrated circuit packaging, multi-chip assembly, optoelectronic system integration, microelectromechanical systems (MEMS), microwave / millimeter wave antennas, and bio-microfluidics due to its optical transparency, high mechanical strength, excellent electrical insulation and chemical corrosion resistance. The overall or partial "conformal" metallization of the glass substrate surface or microstructure surface is the premise and basis for the realization of the above product application functions.
[0004] Electroless plating (ECD) is a wet process driven by an electrochemical mechanism. This wet process is capable of metallizing the surface of non-conductive substrates under specific conditions. ECD metal films are essentially an autocatalytic reaction that does not require an external current, but require trace amounts of precious metals (such as palladium (Pd)) as catalysts to reduce the activation energy of the deposition reaction and promote the kinetics of the metallization deposition reaction. Since metal reduction nucleation occurs at the active sites of the catalyst, the interaction between the catalyst and the substrate is an important factor in determining the adhesion of ECD metal films. Generally, the adhesion of ECD metal films on non-conductive substrates mainly depends on the interfacial roughness generated by the anchoring effect, which is a mechanical bond generated due to the surface microstructure. In order to enhance the adhesion of ECD metal films, when the inherent roughness of the substrate is insufficient, appropriate surface treatment methods such as plasma etching, chip removal or micropatterning can be used to create additional microstructures on the surface. However, since the glass surface is not only very flat but also chemically inert, surface roughening by the above physical or chemical methods usually cannot produce sufficient roughness and thus cannot provide sufficient adhesion. At the same time, due to the high quality requirements for the glass / metal interface in electronic system applications, the excessive "roughening" process used to improve the adhesion of ECD metal films will cause the transmission characteristics of high-frequency circuit system signals to deteriorate significantly. As a result, the relevant process system that improves adhesion by physical and chemical roughening of the glass surface does not have the possibility of practical application. Therefore, poor adhesion (<5N / cm) is the main factor hindering the application of ECD metal films on glass substrates. Fundamentally, due to the different chemical structures, it is difficult to form chemical bonds at the interface between metal and glass, and the covalent oxide network of glass and the metal lattice interface cannot be well bonded.
[0005] Based on the above problems, it is particularly important to seek a surface modification technology before all-wet chemical metal deposition that is convenient, low-cost, widely applicable, and has high adhesion between the deposited metal layer and the glass.
[0006] The present invention proposes a surface modification technology based on a fully wet chemical method, which can perform overall or local "conformal" metallization treatment on a glass substrate and its surface with microstructures or on a microstructured surface. The core of this technology is to prepare an aqueous SAPL molecular dispersion solution, which mainly contains two types of metal oxide nanoparticles with "adhesion promotion" and "autocatalytic activity" and some other additives. The "adhesion promotion" metal oxide forms a strong chemical bond with the surface of the glass substrate so that the SAPL film adheres to the surface of the substrate; the "autocatalytic activity" metal oxide provides active catalytic sites for ECD metal reduction; the role of the additive is to trigger the hydrolysis of the metal salt and regulate the size and stability of the subsequently produced nano metal oxide. Summary of the invention
[0007] The present invention relates to the preparation, film formation and subsequent metal film plating of an aqueous SAPL molecular dispersion solution. The integrated characteristics of the "adhesion promotion" and "autocatalytic activity" functions of the SAPL film are achieved by the "high temperature self-decomposition" and "self-organized crystallization segregation" of the aqueous SAPL molecular dispersion solution system under high temperature treatment conditions. The metal film relies on wet chemical plating metal deposition technology.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] A method for wet chemical metallization of a glass substrate surface comprises the following steps:
[0010] (1) Preparation of aqueous SAPL molecular dispersion solution
[0011] SAPL aqueous molecular dispersion solution includes four components:
[0012] L1: at least one metal salt selected from Ti, Mn, Mg and Zn as an “adhesion promoting” precursor compound;
[0013] L2: at least one metal salt selected from Pd, Ag, Cu and Al as a "self-catalytically active" precursor compound;
[0014] L3: at least one of NaOH, KOH, and NH4OH as a hydrolysis initiator;
[0015] L4: at least one of glacial acetic acid, nitric acid, citric acid, ethanolamine, diethanolamine or triethanolamine as a stabilizer;
[0016] L1 and L2 are mixed with deionized water at a certain concentration to form a metal salt aqueous solution, wherein the concentration of L1 in the metal salt aqueous solution is 0.4-1.2 mol / L, and the concentration of L2 is 5%-10% of L1; then an appropriate amount of L3 is added to hydrolyze it; after stirring, an appropriate amount of L4 is added to adjust the pH to neutral; the mixed solution is placed in a water bath and stirred, and then aged at room temperature for more than 24 hours;
[0017] (2) depositing an aqueous SAPL sol film composed of TiO2, MnO2, MgO or ZnO as an adhesion oxide layer and Pd, Ag, Cu and Al as a catalytically active seed layer on the substrate surface;
[0018] (3) heating the substrate at a temperature higher than 300° C. to form a metal oxide layer SAPL having both “adhesion promotion” and “autocatalytic activity” functions integrated on the surface of the substrate, with a thickness of 50 nm to 600 nm;
[0019] (4) forming a metal film at least 0.5 μm thick to coat the surface of the substrate having the SAPL by wet chemical plating of the metal film;
[0020] (5) The metal coating is heated to a temperature between 180° C. and 250° C. for annealing.
[0021] As a preferred method, after the glass substrate contacts the aqueous SAPL molecular dispersion solution, it self-assembles and adsorbs on the surface of the substrate to form a layer of aqueous sol film, and after pre-sintering to remove water and residual organic matter, a SAPL film is formed; the SAPL film is formed by the fusion of two metal oxides, "adhesion promoting" and "autocatalytically active"; the role of the "adhesion promoting" metal oxide is to form a strong chemical bond on the surface of the glass substrate, so that the SAPL film adheres to the surface of the glass substrate; as the temperature continues to rise, the "autocatalytically active" metal oxide continuously decomposes into oxygen and metal element; while releasing oxygen, the "autocatalytically active" metal is embedded in the "adhesion promoting" metal oxide. The lattice gap of the "promoting" metal oxide is gradually self-organized and crystallized due to the limited gap capacity, forming small-sized nano-metal particles of 5-10nm on the surface of the SAPL film; these nano-particles cannot exist stably at high temperatures, and thus aggregate into large-sized nano-spheres of 200-600nm, providing abundant catalytic active sites for the surface of the SAPL film; at the same time, the oxygen produced by high-temperature decomposition above 300° makes the surface of the SAPL porous; during wet chemical plating, the metal will be deposited in these pores, and the strong mechanical coupling between the metal film and the SAPL film is the main reason for the improvement of the adhesion of the metal film.
[0022] As a preferred embodiment, L1 is selected from one or more of nitrates, chlorides and metal acetates;
[0023] And / or L2 is selected from one or more of metal acetates, nitrates, sulfates and carbonates.
[0024] As a preferred embodiment, L1 is selected from titanium chloride, magnesium nitrate, zinc nitrate and manganese acetate.
[0025] And / or L2 is selected from palladium chloride, silver nitrate, copper acetate, aluminum nitrate.
[0026] As a preferred embodiment, the molar ratio of L3 to L1 is 1:1.
[0027] As a preferred embodiment, the method for forming the aqueous SAPL sol film in step (2) is selected from one of the following methods:
[0028] Ultrasonic bath immersion method: immersion time 5-30min, repeated 2-4 times;
[0029] Pull-up dip coating method: immersion time 1-10 minutes, pull-up speed 2-6cm / min, repeat 4-6 times;
[0030] Spin coating method: The spin coating speed is 4000rpm-6000rpm, the time is 30-60s, and it is repeated 4-8 times.
[0031] As a preferred embodiment, step (3) is divided into two steps:
[0032] (3.1) Pre-sintering time is 10-15min at a temperature between 300-350℃;
[0033] (3.2) Annealing time is 30-90 min at a temperature between 400-600°C.
[0034] As a preferred embodiment, the step (4) is specifically as follows:
[0035] The substrate is contacted with a chemical plating and electroplating aqueous solution containing metal ions to be plated; the chemical plating time is 3-8 minutes, and the electroplating time is 30-60 minutes;
[0036] And / or the wet chemical plating metal solution is a copper plating solution or a nickel plating solution.
[0037] As a preferred embodiment, when the surface of the glass substrate has a microstructure, step (4) includes two pretreatment steps:
[0038] (4.1) placing the microstructured glass substrate coated with the SAPL film in a sodium borohydride reducing solution for treatment;
[0039] (4.2) then immersing the substrate in a complex solution containing only the metal ions to be plated;
[0040] As a preferred embodiment, step (5) is performed by heating to a temperature between 180°C and 250°C for annealing, including the following temperature curve:
[0041] a) Heat to 180°C in a nitrogen atmosphere and keep at 180°C for 30 minutes, or
[0042] b) Heat at 250°C in a nitrogen atmosphere for 20 to 40 minutes.
[0043] Compared with the prior art, the beneficial effects of this invention are:
[0044] Traditional methods use physical vapor deposition (PVD) or chemical vapor deposition (CVD) methods to deposit the adhesion layer and conductive seed layer of the glass substrate. However, processes such as PVD and CVD require low-pressure environments, high temperatures, long process cycles, and limited step coverage. In addition, when the seed layer is deposited on a glass substrate processed with a microstructure, the deposition thickness of the seed layer is significantly unevenly distributed on the sidewalls of the glass substrate with the microstructure. Compared with the flat exposed surface, the seed layer on the sidewalls of the glass substrate with the microstructure is much thinner. In extreme cases, the seed layer will not be deposited at the bottom corners, which will cause gaps to form when the microstructure is filled by electroplating, which is not conducive to subsequent applications. The SAPL film prepared by the present invention can well solve the problem of uniform coverage of the adhesion layer and conductive seed layer of the glass substrate processed with a microstructure, and will have huge advantages in cost.
[0045] The catalytic metal nanoparticles formed by high temperature annealing are evenly distributed on the surface of the SAPL film, making it a catalytically active site. The metal layer can be directly deposited by immersing in a chemical plating solution or an electroplating solution without the need for subsequent sensitization and activation steps.
[0046] The metal film surface prepared by wet chemistry in the present invention is not only uniformly bright, flat and dense, extremely pure and well crystallized, but also provides a metal layer on the glass substrate surface showing high adhesion of the deposited metal layer to the glass and thus forming a durable bonded metal layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] The present invention is further described below in conjunction with the accompanying drawings and embodiments:
[0048] Figure 1 Surface and cross-sectional SEM images of a glass substrate having Zn / Ag-SAPL coating obtained according to the present invention are shown.
[0049] Figure 2 The XRD diffraction patterns of Zn / Ag-SAPL films are shown.
[0050] Figure 3 Shows the XRD diffraction pattern of the copper layer plated on the glass substrate.
[0051] Figure 4 Copper metallization of a cross section of a TGV glass substrate is shown. DETAILED DESCRIPTION
[0052] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0053] The present invention can be directly applied to, but not limited to, the fields of glass substrate surface decoration, high thermal conductivity glass, electrically heated glass, wireless energy glass substrate, electromagnetic shielding glass, electronic substrate glass, glass-based biosensor electrodes and signal transmission layers, integrated circuit packaging substrates, etc. The surface roughness of the glass substrate treated by the method of the present invention can be less than 20nm.
[0054] The embodiment provides a method for wet chemical metallization of a glass substrate surface, comprising the following steps:
[0055] (1) Preparation of aqueous SAPL molecular dispersion solution
[0056] The aqueous SAPL molecular dispersion solution consists of four components:
[0057] L1: at least one metal salt selected from Ti, Mn, Mg and Zn as an “adhesion promoting” precursor compound;
[0058] L2: at least one metal salt selected from Pd, Ag, Cu and Al as a "self-catalytically active" precursor compound;
[0059] L3: at least one of NaOH, KOH, and NH4OH as a hydrolysis initiator;
[0060] L4: at least one of glacial acetic acid, citric acid, nitric acid, ethanolamine, diethanolamine or triethanolamine as a stabilizer;
[0061] L1 and L2 are mixed with deionized water at a certain concentration to form a demetallized salt aqueous solution, wherein the concentration of L1 in the metal salt aqueous solution is 0.4-1.2 mol / L, and the concentration of L2 is 5%-10% of L1; then an appropriate amount of L3 is added to hydrolyze it; after stirring, an appropriate amount of L4 is added to adjust the pH to neutral; the mixed solution is placed in a water bath and stirred, and then aged at room temperature for more than 24 hours;
[0062] (2) depositing an aqueous SAPL sol film composed of TiO2, MnO2, MgO or ZnO as an adhesion oxide layer and Pd, Ag, Cu and Al as a catalytically active seed layer on the substrate surface;
[0063] (3) heating the substrate at a temperature higher than 300° C. to form a metal oxide layer SAPL having both “adhesion promotion” and “autocatalytic activity” functions integrated on the surface of the substrate, with a thickness of 50 nm to 600 nm;
[0064] (4) forming a metal film at least 0.5 μm thick to coat the surface of the substrate having the SAPL by wet chemical plating of the metal film;
[0065] (5) The metal coating is heated to a temperature between 180° C. and 250° C. for annealing.
[0066] After the glass substrate comes into contact with the aqueous SAPL molecular dispersion solution, it self-assembles and adsorbs on the surface of the substrate to form a layer of aqueous sol film. After pre-sintering to remove water and residual organic matter, a SAPL film is formed. The SAPL film is formed by the fusion of two metal oxides, "adhesion promoting" and "autocatalytic activity". The role of the "adhesion promoting" metal oxide is to form a strong chemical bond on the surface of the glass substrate, so that the SAPL film adheres to the surface of the glass substrate. As the temperature continues to rise, the "autocatalytic activity" metal oxide continues to decompose into oxygen and metal element. While releasing oxygen, the "autocatalytic activity" metal is embedded in the "adhesion promoting" metal oxide. Due to the limited capacity of the lattice gaps of metal oxides, the "self-catalytically active" metal gradually self-organizes and crystallizes to form small-sized nanometal particles of 5-10nm on the surface of the SAPL film; these nanoparticles cannot exist stably at high temperatures, and thus aggregate into large-sized nanospheres of 200-600nm, providing abundant catalytic active sites for the surface of the SAPL film; at the same time, the oxygen produced by high-temperature decomposition above 300° makes the surface of the SAPL porous; during wet chemical plating, the metal will be deposited in these pores, and the strong mechanical coupling between the metal film and the SAPL film is the main reason for the improved adhesion of the metal film.
[0067] In some embodiments, L1 is selected from one or more of metal acetates, nitrates, and chlorides;
[0068] And / or L2 is selected from one or more of metal acetates, nitrates, sulfates and carbonates.
[0069] In some embodiments, L1 is selected from titanium chloride, magnesium nitrate, zinc nitrate, and manganese nitrate.
[0070] And / or L2 is selected from palladium chloride, silver nitrate, copper acetate, aluminum nitrate.
[0071] In some embodiments, the molar ratio of L3 to L1 is 1:1.
[0072] In some embodiments, the method for forming the aqueous SAPL sol film in step (2) is selected from one of the following methods:
[0073] Ultrasonic bath immersion method: immersion time 5-30min, repeated 2-4 times;
[0074] Pull-up dip coating method: immersion time 1-10min, pull-up speed 2-6cm / min, repeat 4-6 times;
[0075] Spin coating method: The spin coating speed is 4000rpm-6000rpm, the time is 30-60s, and it is repeated 4-8 times.
[0076] In some embodiments, step (3) is divided into two steps:
[0077] (3.1) Pre-sintering time is 10-15min at a temperature between 300-350℃;
[0078] (3.2) Annealing time is 30-90 min at a temperature between 400-600°C.
[0079] In some embodiments, step (4) is specifically:
[0080] The substrate is contacted with a chemical plating and electroplating aqueous solution containing metal ions to be plated; the chemical plating time is 3-8 minutes, and the electroplating time is 30-60 minutes;
[0081] And / or the wet chemical plating metal solution is a copper plating solution or a nickel plating solution.
[0082] In some embodiments, when the surface of the glass substrate has a microstructure, step (4) includes two steps:
[0083] (4.1) placing the microstructured glass substrate coated with the metal oxide layer SAPL in a sodium borohydride reducing solution for treatment;
[0084] (4.2) then immersing the substrate in a complex solution containing only the metal ions to be plated;
[0085] In some embodiments, step (5) is performed by heating to a temperature between 180° C. and 250° C. for annealing, including the following temperature curve:
[0086] a) Heat to 180°C in a nitrogen atmosphere and keep at 180°C for 30 minutes, or
[0087] b) Heat at 250°C for 20-40 min in a nitrogen atmosphere.
[0088] Embodiment 1:
[0089] Step 1: Prepare Ti / Pd aqueous SAPL molecular dispersion solution
[0090] TiCl4 and PdCl2 are mixed with deionized water in a certain amount to form a demetallized solution. The concentration of TiCl4 in the metal salt aqueous solution is 0.4 mol / L, and the concentration of PdCl2 is 0.02 mol / L. Then, an appropriate amount of NaOH solution (2 g / L) is added to hydrolyze it, wherein the molar ratio of NaOH to TiCl4 is 1:1. After stirring, an appropriate amount of nitric acid solution is added to adjust the pH to neutral. The mixed solution is placed in a 60°C water bath and stirred for 2 hours, and then aged at room temperature for more than 24 hours.
[0091] Step 2: The glass substrate (3cm*3cm*0.5cm) was immersed in a mixture of 70wt.% ethanol and 30wt.% water in an ultrasonic bath for 10min. Then, it was immersed in a mixture of 20wt.% H2O and 80wt.% H2SO4 at 80°C for 20min. Then, the substrate was rinsed with deionized water and vacuum dried. Subsequently, the cleaned glass substrate was immersed in a Ti / Pd aqueous SAPL molecular dispersion solution for 1min. Finally, it was pulled out at a speed of 4cm / min. Thus, a Ti / Pd aqueous SAPL sol film consisting of TiO2 as an adhesion oxide layer and Pd as a catalytically active seed layer was deposited on the surface of the substrate.
[0092] Step 3: Place the substrate in a 300°C tube furnace for pre-sintering for 10 minutes, take it out and cool it to room temperature. Repeat the pulling and pre-sintering steps six times. Then, heat it to 500°C in a 300°C tube furnace at a heating rate of 5°C / min and hold it for 1 hour. Finally, slowly cool it to room temperature and take it out, rinse it with deionized water for 1-2 minutes. Thus, a Ti / Pd-SAPL with integrated "adhesion promotion" and "self-catalytic activity" functions is formed on the surface of the substrate, with a thickness of 50nm-600nm.
[0093] Step 4: Prepare chemical copper plating solution (chemical copper plating bath can be purchased from Shenzhen Shunxin Fine Chemical Co., Ltd.). Heat the water bath to raise the temperature of the plating solution to 50°C. Then, place the glass substrate coated with Ti / Pd-SAPL film into the chemical copper plating solution. After deposition for 5-10 minutes, take out the substrate and rinse it with deionized water. Finally, immerse the substrate in a 50°C electrolytic copper plating solution containing copper pyrophosphate (electrolytic copper plating bath can be purchased from Shenzhen Shunxin Fine Chemical Co., Ltd.) at 5A / dm 2 The current density is electroplated for 30-35 minutes. After the electroplating is completed, the substrate is taken out and rinsed with deionized water for 1-2 minutes. Thus, a metal film at least 0.5 μm thick is formed to coat the surface of the substrate with Ti / Pd-SAPL by a wet chemical plating method of a conductive metal film.
[0094] Step 5: annealing the glass substrate coated with the metal copper layer in a nitrogen atmosphere at a temperature of 180° C. for 30 minutes.
[0095] Embodiment 2:
[0096] Step 1: Prepare Mg / Pd aqueous SAPL molecular dispersion solution
[0097] Mg(NO3)2 and PdCl2 are mixed with deionized water in a certain amount to form a metal salt aqueous solution, wherein the concentration of Mg(NO3)2 in the metal salt aqueous solution is 0.4 mol / L, and the concentration of PdCl2 is 0.02 mol / L. Subsequently, an appropriate amount of NaOH solution (2 g / L) is added to hydrolyze it, wherein the molar ratio of NaOH to Mg(NO3)2 is 1:1. After stirring, an appropriate amount of nitric acid solution is added to adjust the pH to neutral. The mixed solution is placed in a 60°C water bath and stirred for 2 hours, and then aged at room temperature for more than 24 hours.
[0098] Step 2: The glass substrate (3cm*3cm*0.5cm) was immersed in a mixture of 70wt.% ethanol and 30wt.% water in an ultrasonic bath for 10min. Then, it was immersed in a mixture of 20wt.% H2O and 80wt.% H2SO4 at 80°C for 20min. Then, the substrate was rinsed with deionized water and vacuum dried. Finally, the Mg / Pd aqueous SAPL molecular dispersion solution was dropped on the clean glass substrate surface by spin coating at a speed of 4000rpm for 3min. A Mg / Pd aqueous SAPL sol film consisting of MgO as an adhesion oxide layer and Pd as a catalytically active seed layer was deposited on the substrate surface.
[0099] Step 3: Place the substrate in a 300°C tube furnace for pre-sintering for 10 minutes, take it out and cool it to room temperature. Repeat the spin coating and pre-sintering operations eight times. Then, heat it to 500°C at a heating rate of 5°C / min in a 300°C tube furnace and keep it for 1 hour. Finally, slowly cool it to room temperature, take it out and rinse it with deionized water for 1-2 minutes. Thus, a Mg / Pd-SAPL with integrated "adhesion promotion" and "self-catalytic activity" functions is formed on the surface of the substrate, with a thickness of 50nm-600nm.
[0100] Step 4: Prepare an electroless copper plating solution (an electroless copper plating bath that can be purchased from Shenzhen Shunxin Fine Chemical Co., Ltd.). Heat the plating solution in a water bath to 50°C. Then, place the glass substrate coated with the Mg / Pd-SAPL film in the electroless copper plating solution for 5 minutes, remove the substrate and rinse it with deionized water. Finally, immerse the substrate in a 50°C plating solution containing copper pyrophosphate (an electrolytic copper plating bath that can be purchased from Shenzhen Shunxin Fine Chemical Co., Ltd.) at 5A / dm 2The current density is 0.5000 nm and the electroplating time is 30-35 minutes. After the electroplating, the substrate is taken out and rinsed with deionized water for 1-2 minutes. Thus, a metal film with a thickness of at least 0.5 μm is formed to coat the surface of the substrate with Mg / Pd-SAPL by a wet chemical metal film plating method.
[0101] Step 5: annealing the glass substrate coated with the metal copper layer in a nitrogen atmosphere at a temperature of 180° C. for 30 minutes.
[0102] Embodiment 3:
[0103] Step 1: Prepare Zn / Ag aqueous SAPL molecular dispersion solution
[0104] Mix a certain amount of Zn(NO3)2 and AgNO3 with deionized water to form a demetallized salt solution. The concentration of Zn(NO3)2 in the metal salt aqueous solution is 0.4 mol / L, and the concentration of AgNO3 is 0.02 mol / L. Subsequently, add an appropriate amount of NaOH solution (2 g / L) to hydrolyze it, where the molar ratio of NaOH to Zn(NO3)2 is 1:1. After stirring, add an appropriate amount of glacial acetic acid solution to adjust the pH to neutral. Place the mixed solution in a 70°C water bath and stir for 2 hours, then age it at room temperature for more than 24 hours.
[0105] Step 2: The TGV glass substrate (through hole size: 32 μm diameter * 320 μm thickness) was immersed in a mixture of 70 wt.% ethanol and 30 wt.% water in an ultrasonic bath for 10 minutes. Then, it was immersed in a mixture of 20 wt.% H2O and 80 wt.% H2SO4 at 80°C for 20 minutes. Next, the substrate was ultrasonically bathed in deionized water for 10 minutes and vacuum dried. Finally, the cleaned TGV glass substrate was immersed in a Zn / Ag aqueous SAPL molecular dispersion solution and ultrasonically bathed for 10 minutes. Thus, a Zn / Ag aqueous SAPL sol film composed of ZnO as an adhesion oxide layer and Ag as a catalytically active seed layer was deposited on the surface of the substrate.
[0106] Step 3: Place the substrate in a 350°C tube furnace and sinter for 10 minutes, then take it out and cool it to room temperature. Repeat the ultrasonic bath dip coating and pre-sintering operations four times. Then, heat it to 500°C in a 300°C tube furnace at a heating rate of 5°C / min and anneal for 1h. Finally, slowly cool it to room temperature and take it out, rinse it with deionized water for 1-2min. Thus, a Zn / Ag-SAPL with integrated "adhesion promotion" and "self-catalytic activity" functions is formed on the surface of the substrate, with a thickness of 50nm-600nm.
[0107] Step 4: First, immerse the TGV glass substrate coated with the Zn / Ag-SAPL film in a reducing solution of sodium borohydride for 5 minutes. Subsequently, rinse the substrate with deionized water for 1-2 minutes, immerse it in a copper sulfate solution (0.5 mol / L), and ultrasonic bath for 10 minutes. Finally, prepare an electroless copper plating solution (an electroless copper plating bath available from Shenzhen Shunxin Fine Chemical Co., Ltd.), and heat the solution to 50°C. Place the substrate in the electroless copper plating solution for deposition for 10 minutes, take out the substrate and rinse it with deionized water. Thus, by the method of wet chemical plating of a conductive metal film, a metal film at least 0.5 μm thick is formed to coat the surface of the substrate having Zn / Ag-SAPL.
[0108] Step 5: annealing the glass substrate coated with the metal copper layer in a nitrogen atmosphere at a temperature of 250° C. for 30 minutes.
[0109] Embodiment 4:
[0110] Step 1: Prepare Mn / Ag aqueous SAPL molecular dispersion solution
[0111] Mix (CH3COO)2Mn and AgNO3 in a certain amount with deionized water to form a metal salt aqueous solution. The concentration of (CH3COO)2Mn in the deionized water solution is 0.4mol / L, and the concentration of AgNO3 is 0.02mol / L. Subsequently, add an appropriate amount of NaOH solution (2mol / L) to hydrolyze it. After stirring, add an appropriate amount of citric acid solution (3mol / L) to adjust the pH to neutral. Place the mixed solution in a 70℃ water bath and stir for 2h, then age it at room temperature for more than 24 hours.
[0112] Step 2: The TGV glass substrate (blind hole size: 50 μm diameter * 300 μm thickness) was immersed in a mixture of 70 wt.% ethanol and 30 wt.% water in an ultrasonic bath for 10 minutes. Then, it was immersed in a mixture of 20 wt.% H2O and 80 wt.% H2SO4 at 80°C for 20 minutes. Next, the substrate was ultrasonically bathed in deionized water for 10 minutes and vacuum dried. Finally, the cleaned TGV glass substrate was immersed in a Mn / Ag aqueous SAPL molecular dispersion solution and ultrasonically bathed for 10 minutes. Thus, a Mn / Ag aqueous SAPL sol film consisting of MnO2 as an adhesion oxide layer and Ag as a catalytically active seed layer was deposited on the substrate surface.
[0113] Step 3: Place the substrate in a 350°C tube furnace and sinter for 10 minutes, then take it out and cool it to room temperature. Repeat the immersion and pre-sintering operations twice. Then, heat it to 550°C in a 350°C tube furnace at a heating rate of 5°C / min and keep it for 1 hour. Finally, slowly cool it to room temperature and take it out, and rinse it with deionized water for 1-2 minutes. Thus, a metal oxide layer SAPL with integrated "adhesion promotion" and "self-catalytic activity" functions is formed on the surface of the substrate, with a thickness of 50nm-600nm.
[0114] Step 4: First, immerse the TGV glass substrate coated with the Mn / Ag-SAPL film in a reducing solution of NaBH4 (2g / L) for 5 minutes. Then, rinse the substrate with deionized water for 1-2 minutes. Subsequently, immerse the TGV glass substrate in a copper sulfate solution (0.5mol / L) and ultrasonic bath for 10 minutes. Finally, prepare an electroless copper plating solution (an electroless copper plating bath that can be purchased from Shenzhen Shunxin Fine Chemical Co., Ltd.) and heat the solution to 50°C. Place the TGV glass substrate in the electroless copper plating solution for deposition for 10 minutes, take out the substrate and rinse it with deionized water. Thus, by the method of wet chemical plating of a conductive metal film, a metal film at least 0.5μm thick is formed to coat the surface of the substrate having Mn / Ag-SAPL.
[0115] Step 5: annealing the glass substrate coated with the metal copper layer in a nitrogen atmosphere at a temperature of 250° C. for 30 minutes.
[0116] Embodiment 5:
[0117] Step 1: Prepare Ti-Zn / Pd aqueous SAPL molecular dispersion solution
[0118] TiCl4, Zn(NO3)2 and PdCl2 are mixed with deionized water in a certain amount to form a metal salt aqueous solution. The concentration of TiCl4 in the metal salt aqueous solution is 0.4mol / L, the concentration of Zn(NO3)2 is 0.2mol / L, and the concentration of PdCl2 is 0.03mol / L. Then add an appropriate amount of NaOH solution (2mol / L) to hydrolyze it, where the molar ratio of NaOH to TiCl4 is 1.5:1. After stirring, add an appropriate amount of nitric acid solution to adjust the pH to neutral. Place the mixed solution in a 60℃ water bath and stir for 2h, then age it at room temperature for more than 24 hours.
[0119] Step 2: The glass substrate (3cm*3cm*0.5cm) was immersed in a mixture of 70wt.% ethanol and 30wt.% water in an ultrasonic bath for 10min. Then, it was immersed in a mixture of 20wt.% H2O and 80wt.% H2SO4 at 80°C for 20min. Then, the substrate was rinsed in deionized water and vacuum dried. Finally, the Ti-Zn / Pd aqueous SAPL molecular dispersion solution was dropped on the clean glass substrate surface by spin coating at a speed of 4000rpm for 3min. Thus, a Ti-Zn / Pd aqueous SAPL sol film composed of TiO2 and ZnO as an adhesion oxide layer and Pd as a catalytically active seed layer was deposited on the substrate surface.
[0120] Step 3: Place the substrate in a 300°C tube furnace for pre-sintering for 10 minutes, take it out and cool it to room temperature. Repeat the spin coating and pre-sintering operations eight times. Then, heat it to 500°C in a 300°C tube furnace at a heating rate of 5°C / min and keep it for 1 hour. Finally, slowly cool it to room temperature and take it out, rinse it with deionized water for 1-2 minutes. Thus, a Ti-Zn / Pd-SAPL with integrated "adhesion promotion" and "self-catalytic activity" functions is formed on the surface of the substrate, with a thickness of 50nm-600nm.
[0121] Step 4: Prepare an electroless copper plating solution (an electroless copper plating bath that can be purchased from Shenzhen Shunxin Fine Chemical Co., Ltd.). Next, heat the water bath to raise the temperature of the plating solution to 50°C. Subsequently, place the glass substrate coated with the Ti-Zn / Pd-SAPL film into the electroless copper plating solution for 5 minutes, remove the substrate and rinse it with deionized water. Finally, immerse the substrate in a 50°C plating solution containing copper pyrophosphate (an electrolytic copper plating bath that can be purchased from Shenzhen Shunxin Fine Chemical Co., Ltd.) at 5A / dm 2 The current density was set to 0.500 nm and the electroplating time was 30 min. After the electroplating, the substrate was taken out and rinsed with deionized water for 1-2 min. Thus, a metal film at least 0.5 μm thick was formed to coat the surface of the substrate having Ti-Zn / Pd-SAPL by wet chemical plating of a conductive metal film.
[0122] Step 5: annealing the glass substrate coated with the metal copper layer in a nitrogen atmosphere at a temperature of 180° C. for 30 minutes.
[0123] Embodiment 6:
[0124] Step 1: Prepare Zn / Pd-Ag aqueous SAPL molecular dispersion solution
[0125] Zn(NO3)2, PdCl2 and AgNO3 are mixed with deionized water in a certain amount to form a metal salt aqueous solution. The concentration of Zn(NO3)2 in the metal salt aqueous solution is 0.6mol / L, the concentration of PdCl2 is 0.015mol / L, and the concentration of AgNO3 is 0.015mol / L. Then, an appropriate amount of NaOH solution (2g / L) is added to hydrolyze it, wherein the molar ratio of NaOH to Zn(NO3)2 is 1:1. After stirring, an appropriate amount of nitric acid solution is added to adjust the pH to neutral. The mixed solution is placed in a 60°C water bath and stirred for 2h, and then aged at room temperature for more than 24 hours.
[0126] Step 2: The glass substrate (3cm*3cm*0.5cm) was immersed in a mixture of 70wt.% ethanol and 30wt.% water in an ultrasonic bath for 10min. Then, it was immersed in a mixture of 20wt.% H2O and 80wt.% H2SO4 at 80°C for 20min. Then, the substrate was rinsed with deionized water and vacuum dried. Finally, the Zn / Pd-Ag aqueous SAPL molecular dispersion solution was dropped on the clean glass substrate surface by spin coating at a speed of 4000rpm for 3min. Thus, a Zn / Pd-Ag aqueous SAPL sol film composed of ZnO as an adhesion oxide layer and Pd and Ag as catalytically active seed layers was deposited on the substrate surface.
[0127] Step 3: Place the substrate in a 300°C tube furnace for pre-sintering for 10 minutes, take it out and cool it to room temperature. Repeat the spin coating and pre-sintering operations eight times. In a 300°C tube furnace, heat to 500°C at a heating rate of 5°C / min and hold for 1 hour. Slowly cool to room temperature and take it out, rinse with deionized water for 1-2 minutes. Thus, a Zn / Pd-Ag-SAPL with integrated "adhesion promotion" and "self-catalytic activity" functions is formed on the surface of the substrate, with a thickness of 50nm-600nm.
[0128] Step 4: Prepare an electroless copper plating solution (an electroless copper plating bath that can be purchased from Shenzhen Shunxin Fine Chemical Co., Ltd.) and heat the solution to 50°C. Subsequently, place the glass substrate coated with the Zn / Pd-Ag-SAPL film in the electroless copper plating solution for 5 minutes, remove the substrate and rinse it with deionized water. Finally, immerse the substrate in a 50°C plating solution containing copper pyrophosphate (an electrolytic copper plating bath that can be purchased from Shenzhen Shunxin Fine Chemical Co., Ltd.) at 5A / dm 2 The current density was set to 0.500 nm and the electroplating time was 30 min. After the electroplating, the substrate was taken out and rinsed with deionized water for 1-2 min. A metal film with a thickness of at least 0.5 μm was formed to coat the surface of the substrate with Zn / Pd-Ag-SAPL by wet chemical plating of the metal film.
[0129] Step 5: annealing the glass substrate coated with the metal copper layer in a nitrogen atmosphere at a temperature of 180° C. for 30 minutes.
[0130] Examples 7-10
[0131] The differences between Examples 7-10 and Example 1 are shown in Table 1.
[0132] from Figure 1 From the SEM image of a, it can be seen that the surface of the Zn / Ag-SAPL coated glass substrate is covered with quasi-spherical particles of different sizes (300-600 nm). Figure 1 b shows the SEM cross-sectional image of Zn / Ag-SAPL / glass, showing a Zn / Ag-SAPL film thickness of 160 nm with a very flat and smooth interface.
[0133] Figure 2 The XRD diffraction patterns of the Zn / Ag-SAPL film surface at annealing temperature of 500°C are shown. Zn / Ag-SAPL exhibits characteristic diffraction peaks corresponding to zinc oxide in the wurtzite structure (JCPDS card number 79-2205). It is worth noting that the SAPL film shows an additional peak at 2θ38.18°, which is attributed to the face-centered cubic (fcc) phase of metallic silver (JCPDS card number 87-0717). These results indicate that not only zinc oxide has good crystallinity, but also confirm that silver nanoparticles are also distributed on the surface of the Zn / Ag-SAPL film.
[0134] After chemical copper plating, Figure 3 It is shown that XRD analysis of the copper layer confirms the excellent crystallinity and there is no other impurities in the copper layer.
[0135] like Figure 4 It shows that after 20 minutes of wet chemical copper plating, the sidewalls and surfaces of the TGV through-holes are completely covered with a metal copper film without clogging or blistering. The surface thickness is about 9μm and the hole wall thickness is about 5μm.
[0136] Table 1 Raw material types and process parameters of each embodiment
[0137]
[0138]
[0139]
[0140] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for wet chemical metallization of a glass substrate surface, characterized in that The following steps are involved: (1) Preparation of aqueous SAPL molecular dispersion solution The aqueous SAPL molecular dispersion solution consists of four components: L1: at least one metal salt selected from Ti, Mn, Mg and Zn as an "adhesion promoting" precursor compound; L2: at least one metal salt selected from Pd, Ag, Cu and Al as a "self-catalytically active" precursor compound; L3: at least one of NaOH, KOH, and NH4OH as a hydrolysis initiator; L4: at least one of glacial acetic acid, nitric acid, citric acid, ethanolamine, diethanolamine or triethanolamine as a stabilizer; L1 and L2 are mixed with deionized water at a certain concentration to form a metal salt aqueous solution, wherein the concentration of L1 in the metal salt aqueous solution is 0.4-1.2 mol / L, and the concentration of L2 is 5%-10% of L1; then an appropriate amount of L3 is added to hydrolyze it; after stirring, an appropriate amount of L4 is added to adjust the pH to neutral; The mixed solution was placed in a water bath and stirred, and then aged at room temperature for more than 24 hours; (2) depositing an aqueous SAPL sol film composed of TiO2, MnO2, MgO or ZnO as an adhesion oxide layer and Pd, Ag, Cu and Al as a catalytically active seed layer on the substrate surface; (3) heating the substrate at a temperature higher than 300° C. to form a metal oxide layer SAPL having both “adhesion promotion” and “autocatalytic activity” functions on the surface of the substrate, with a thickness of 50 nm to 600 nm; (4) forming a metal film at least 0.5 μm thick to coat the surface of the substrate having the SAPL by wet chemical plating of the metal film; (5) The metal coating is heated to a temperature between 180° C. and 250° C. for annealing.
2. A method for wet chemical metallization of a glass substrate surface according to claim 1, characterized in that: After the glass substrate contacts the aqueous SAPL molecular dispersion solution, it self-assembles and adsorbs on the surface of the substrate to form a layer of aqueous sol film. After pre-sintering to remove water and residual organic matter, a SAPL film is formed. The SAPL film is formed by the fusion of two metal oxides, "adhesion promoting" and "autocatalytic activity". The role of the "adhesion promoting" metal oxide is to form a strong chemical bond on the surface of the glass substrate, so that the SAPL film adheres to the surface of the glass substrate. As the temperature continues to rise, the "autocatalytic activity" metal oxide continues to decompose into oxygen and metal element. While releasing oxygen, the "autocatalytic activity" metal is embedded in the "adhesion promoting" metal oxide. Due to the limited capacity of the lattice gap of the metal oxide, the "self-catalytically active" metal gradually self-organizes and crystallizes to form small-sized nano-metal particles of 5-10nm on the surface of the SAPL film; these nano-particles cannot exist stably at high temperatures, and thus aggregate into large-sized nano-spheres of 200-600nm, providing abundant catalytic active sites for the surface of the SAPL film; at the same time, the oxygen produced by high-temperature decomposition above 300° makes the surface of the SAPL porous; during wet chemical plating, the metal will be deposited in these pores, and the strong mechanical coupling between the metal film and the SAPL film is the main reason for the improvement of the adhesion of the metal film.
3. A method for wet chemical metallization of a glass substrate surface according to claim 1, characterized in that: L1 is selected from one or more of nitrates, chlorides and metal acetates; And / or L2 is selected from one or more of metal acetates, nitrates, sulfates and carbonates.
4. A method for wet chemical metallization of a glass substrate surface according to claim 1, characterized in that: L1 is selected from titanium chloride, magnesium nitrate, zinc nitrate, and manganese acetate; And / or L2 is selected from palladium chloride, silver nitrate, copper acetate, aluminum nitrate.
5. A method for wet chemical metallization of a glass substrate surface according to claim 1, characterized in that: The molar ratio of L3 to L1 is 1:
1.
6. A method for wet chemical metallization of a glass substrate surface according to claim 1, characterized in that: The method for forming the aqueous SAPL sol film in step (2) is selected from one of the following methods: Ultrasonic bath immersion method: immersion time 5-30min, repeated 2-4 times; Pull-up dip coating method: immersion time 1-10 minutes, pull-up speed 2-6cm / min, repeat 4-6 times; Spin coating method: The spin coating speed is 4000rpm-6000rpm, the time is 30-60s, and it is repeated 4-8 times.
7. A method for wet chemical metallization of a glass substrate surface according to claim 1, characterized in that: Step (3) is divided into two steps: (3.1) Pre-sintering time is 10-15min at a temperature between 300-350℃; (3.2) Annealing time is 30-90 min at a temperature between 400-600°C.
8. A method for wet chemical metallization of a glass substrate surface according to claim 1, characterized in that: The step (4) is specifically as follows: The substrate is contacted with a chemical plating and electroplating aqueous solution containing metal ions to be plated; the chemical plating time is 3-8 minutes, and the electroplating time is 30-60 minutes; And / or the wet chemical plating metal solution is a copper plating solution or a nickel plating solution.
9. A method for wet chemical metallization of a glass substrate surface according to claim 1, characterized in that: When the glass substrate surface has a microstructure, step (4) includes two pretreatment steps: (4.1) placing the microstructured glass substrate coated with the SAPL film in a sodium borohydride reducing solution for treatment; (4.2) The substrate is then immersed in a complex solution containing only the metal ions to be plated.
10. A method for wet chemical metallization of a glass substrate surface according to claim 1, characterized in that: Step (5) heating to 180°C-250°C for annealing, including the following temperature curve: a) Heat to 180°C in a nitrogen atmosphere and keep at 180°C for 30 minutes, or b) Heat at 250°C in a nitrogen atmosphere for 20 to 40 minutes.
